Comparison of Bronchodilator Response of Nebulized Salbutamol with Nebulized Salbutamol and Ipratropium Bromide in Patients with Acute Exacerbation of Advanced COPD - Hasan, Md Aminul; Sheherin, Sonia; Hossain Sardar, Md Amzad; amin, Md Ruhul; Habib, Md Ahsan; Ahamed, Foysal (TAJ: Journal of Teachers Association, 2022)
Background: Patients admitted with acute exacerbation of Chronic Obstructive Pulmonary Disease (COPD) are often prescribed ipratropium bromide in combination with a β2 agonist like salbutamol. Many studies have not shown any benefit in adding ipratropium bromide to salbutamol in acute exacerbations of COPD. Objectives: To compare the response of combination therapy with two drugs vs. salbutamol alone in the treatment of acute exacerbations of COPD during hospital admission. Materials and Methods: This cross-sectional comparative study was conducted among one hundred patients of acute exacerbation of COPD admitted in Rajshahi Medical College Hospital from January 2012 to July 2012. The patients were randomly allocated to receive either solution-1 (salbutamol 5mg alone) or solution-2 (salbutamol 5mg plus ipratropium bromide 500μgm) (all four times a day) on admission. All other treatment was prescribed at the discretion of the attending physician.FEV1 and FVC values at baseline, at 1 hour, on day 1, day three, and on discharge date were assessed. Patients completed a subjective symptom score at 1 hour, Day 1, Day 3, and on the discharge date. Length of stay in hospital was assessed. Results: There was no significant difference in spirometric values at 1 hour, Day 1, Day 3, and during discharge between the two groups. The subjective improvement was similar with both treatments. There was no difference between the two groups in the mean (±SD) length of hospital stay (salbutamol 5.98(±1.67) days, salbutamol plus ipratropium bromide 5.8(±1.39) days; t=0.586, p>0.05). Conclusion: The routine addition of nebulized ipratropium bromide to salbutamol appears to be of no benefit in the treatment of acute exacerbations of COPD. TAJ 2021; 34: No-2: 56-63